An educational system with functions of guidance and adaptive advice to support problem solving based on basic concepts of statistics (International Conference on Computers in Education, 2020)
Recently, statistics is a necessary subject not only for experts but for common people as well. In the field of education on statistics, it is required to present that improve learners’ motivation and promote deep understanding. We thought that problems using statistical concepts on the real world can satisfy such a condition. In this study, we have developed a educational system equipped with a guidance function that asks learners such questions and organizes data, and an adaptive advice function that gives advice according to the type of the wrong answer. Learners tackle the problem using our system and system-independent statistical tools. In addition, we conducted an evaluation experiment to evaluate the usefulness of the system. The results showed that the guidance function and the advisory function of this system are effective for improving the exercise achievement rate for the learner to proceed with learning, and that the learner feels that the acquired knowledge is useful.